Neurovascular Inflammation and Oxidative Stress Markers in Chronic Migraine: Is Nitric Oxide the Key Link to Severity? - Aulia Noza; Restu Susanti; Yuliarni Syafrita; Syarif Indra; Lydia Susanti; Reno Bestari (HM Publisher, 2025)
Background: Nitric oxide (NO), a ubiquitous signaling molecule, has been implicated in migraine pathophysiology through mechanisms including vasodilation, neurogenic inflammation, and oxidative stress. However, its specific relationship with the clinical severity of chronic migraine required further elucidation. This study aimed to investigate the association between serum NO levels and the severity of chronic migraine in a cohort of female patients. Methods: An observational study employing a cross-sectional design was conducted between July 2024 and November 2024 at Neurology Clinics and Community Healthcare Centers in Padang City, Indonesia. Fifty-one female chronic migraineurs, diagnosed according to ICHD-3 criteria, were enrolled using consecutive sampling. Patients with specific comorbidities, pregnancy, breastfeeding, or Medication Overuse Headache (MOH) were excluded. Migraine severity during an ictal phase was assessed using the Migraine Severity Scale (MIGSEV). Venous blood samples were collected during migraine attacks (ictal phase), and serum NO levels were quantified using a colorimetric method. The association between NO levels and MIGSEV scores was analyzed using the Kruskal-Wallis test, followed by post-hoc Mann-Whitney U tests. Statistical significance was set at p < 0.05. Results: The study included 51 female chronic migraineurs with a median age of 33 years. Migraine severity distribution was: 10 (19.6%) mild, 26 (51.0%) moderate, and 15 (29.4%) severe. The overall median serum NO level was 74.8 nmol/ml (range: 32.20 - 169.15 nmol/ml). Median NO levels demonstrated a positive gradient with increasing migraine severity: mild group 47.31 nmol/ml (range: 34.85 - 67.15), moderate group 88.45 nmol/ml (range: 32.20 - 167.45), and severe group 96.71 nmol/ml (range: 65.45 - 169.15). The Kruskal-Wallis test revealed a statistically significant difference in NO levels across the severity groups (p < 0.01). Post-hoc analyses confirmed significant differences between the mild and moderate groups (p < 0.01) and between the mild and severe groups (p < 0.01). Conclusion: This study demonstrated a significant positive association between serum Nitric Oxide levels, measured during the ictal phase, and the severity of chronic migraine in female patients. Higher NO levels were correlated with greater migraine severity, suggesting NO may play a crucial role in the mechanisms underlying migraine intensity and potentially serve as a biomarker reflecting the clinical burden of chronic migraine.